2022
DOI: 10.1039/d1ce01544c
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pressure on the phase transformations and mechanical properties of 10 mol% Mg-PSZ sintered by HPHT

Abstract: MgO (10 mol%)-stabilized zirconia ceramics were obtained using high-pressure high-temperature (HPHT) sintering. The effects of the sintering pressure (2.5, 3.7, and 5.0 GPa) on the phase transformations and hardness were...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…ZrO 2 has a high level of chemical stability due to the oxygen‐zirconium bond strength, which is comparable to that of silicon oxide. While silicon oxide has an oxygen coordination number of 4, ZrO 2 has an oxygen coordination number of more than 7 22 . A related study showed that ZrO 2 was able to maintain its stability for up to 3 h after being submerged in a solution of extremely concentrated NaOH 23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ZrO 2 has a high level of chemical stability due to the oxygen‐zirconium bond strength, which is comparable to that of silicon oxide. While silicon oxide has an oxygen coordination number of 4, ZrO 2 has an oxygen coordination number of more than 7 22 . A related study showed that ZrO 2 was able to maintain its stability for up to 3 h after being submerged in a solution of extremely concentrated NaOH 23 .…”
Section: Introductionmentioning
confidence: 99%
“…While silicon oxide has an oxygen coordination number of 4, ZrO 2 has an oxygen coordination number of more than 7. 22 A related study showed that ZrO 2 was able to maintain its stability for up to 3 h after being submerged in a solution of extremely concentrated NaOH. 23 The high melting point, corrosion resistance, and wear resistance of ZrO 2 have resulted in its wide use in various material fields such as ceramics, solid battery materials, catalytic materials, and adsorbent materials.…”
Section: Introductionmentioning
confidence: 99%